2003
DOI: 10.22621/cfn.v117i2.678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Cover Improvements for Nesting Ducks on Grassland Songbirds

Abstract: Filion. 2003. Effects of plant cover improvements for nesting ducks on grassland songbirds. Canadian Field-Naturalist 117(2): 167-172.Several islands located along the St. Lawrence River in southern Quebec have been used as natural pastureland by cattle for decades. Recently, a rest-rotation grazing system and dense nesting cover were established on four islands near Varennes to improve duck nesting conditions. The effects of these two plant cover improvements on the abundance of grassland songbirds were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Bollinger (1995) found a positive relationship between presence of grass and blackbirds, and Camp and Best (1994) found a positive relationship between grass cover and nest densities. Other studies have shown that Red-winged Blackbirds favor dense vegetation (LaPointe et al 2003); Albers (1978) found that blackbird territories had significantly taller, denser vegetation than unused areas, and Bollinger (1995) found that Red-winged Blackbirds were most abundant in fields with dense cover. However, in a survey of Illinois grassland species, Herkert ( 1 994) found no correlates of vegetation structure and occupancy by Red-winged Blackbirds, which were present on 93% of his transects, and Scott et al (2002) found that blackbirds were negatively associated with grass cover on reclaimed surface mines in Indiana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bollinger (1995) found a positive relationship between presence of grass and blackbirds, and Camp and Best (1994) found a positive relationship between grass cover and nest densities. Other studies have shown that Red-winged Blackbirds favor dense vegetation (LaPointe et al 2003); Albers (1978) found that blackbird territories had significantly taller, denser vegetation than unused areas, and Bollinger (1995) found that Red-winged Blackbirds were most abundant in fields with dense cover. However, in a survey of Illinois grassland species, Herkert ( 1 994) found no correlates of vegetation structure and occupancy by Red-winged Blackbirds, which were present on 93% of his transects, and Scott et al (2002) found that blackbirds were negatively associated with grass cover on reclaimed surface mines in Indiana.…”
Section: Discussionmentioning
confidence: 99%
“…near the Missouri River. Numerous researchers have investigated habitat selection by Red-winged Blackbirds (Albers 1978, Joyner 1978, Pribill and Pieman 1997, Turner and McCarthy 1998, and some have examined responses of Red-winged Blackbirds and other species within plots characterized by differing management regimes (Herkert 1994, McCoy et al 2001, LaPointe et al 2003; however, our study is the only one we know of in which more than one factor varied (i.e., perch availability and grass cover) among adjoining treatment plots within the same sites. These plots varied with respect to densities of planted trees, which blackbirds used as perches, and the presence or absence of a planted cover crop.…”
mentioning
confidence: 99%
“…In Oklahoma however, though field sparrow nests in PBG treatment pastures were fewer than in traditional control grazing pastures, the effects were not significant and overall success (17.6%) was comparable to reported ranges ( Holcomb, Davis & Fuhlendorf, 2014 ). Finally, red-winged blackbird nest densities were greater in idle and cattle exclusion treatment fields, than in those that included experimental disturbances ( Lapointe et al, 2003 ). Even thought we did not document a treatment effect indigo bunting DSR, our results were similar to previous reported DSR (∼93–96%) ( Weldon, 2006 ).…”
Section: Discussionmentioning
confidence: 99%